TINJAUAN HUKUM TENTANG PEMUTIHAN PINJAMAN AKIBAT DEBITUR MENINGGAL DUNIA - Sianturi, Tri Saputra Marojahan; Roida Nababan; Lesson Sihotang (Magister Hukum Universitas HKBP Nommensen, 2024)
This study aims to determine the principle of prudence in providing credit at the Panitonga branch of Bank Rakyat Indonesia and to find out what causes credit whitening if the debtor dies at the Panitonga branch of Bank Rakyat Indonesia. The type of research used is Field Research (Interview) and Library Research (library) and materials related to the law regarding credit whitening due to the death of the debtor. The principle of prudence in lending to Bank Rakyat Indonesia Panitonga is to maintain the soundness of the bank with the provisions of capital requirements, asset quality, management quality, liquidity, profitability, solvency, and other aspects related to the bank with the provisions and implementation of the 5C principles and & 7P. Credit whitening carried out at the BRI Panitonga branch when the debtor dies due to a loan insurance which is in accordance with the provisions of the insurance policy, if the debtor dies, the insurance covers/pays the remaining credit from the side debtor, so that the debtor's heirs are not burdened with credit payments of the deceased debtor.